Improving business processes in a globally dispersed make-to-order supply chain. Case study on outbound logistics in a Multinational Corporation - Hurskainen, Maisa (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The purpose of this thesis is to find out how outbound logistics process can be improved by reducing unnecessary waste in a globally dispersed make-to-order (MTO) supply chain. The research problem was addressed by a multinational corporation that aims to find a solution for reducing unnecessary waste in their outbound logistics process. The focus is on customized products that are delivered via sea transportation. Theoretical framework for improving outbound logistics processes in globally dispersed MTO supply chain was created based on business process management, Porter’s value chain theory, value stream mapping and current reality tree. The empirical research was conducted by using constructive approach due to its ability to research a practical problem and to improve the existing practices. The data was collected from ten semi-structured interviews and three non-participant observations. By analysing the data and applying the theoretical framework, five types of waste were detected in the process that were seen to derive from six root causes. Practical solution was constructed to reduce the waste in the process by combining the existing literature with the ideas raising from empirical data. The results of this thesis suggest that a MNC with a globally dispersed MTO supply chain can improve its outbound logistics process by applying activities that enhance internal and external integration, collaboration and coordination, and increase predictability of the process. This research has practical relevance both for the case company as well as for other MNCs with globally dispersed MTO supply chains that aim to improve their outbound logistics processes. This research contributes to the BPM and CRA research by providing an evidence for their applicability in the new context.

Tutkimuksen tavoitteena on selvittää, miten lähtölogistiikkaa voidaan parantaa vähentämällä tarpeetonta hukkaa globaalisti hajaantuneessa MTO-toimitusketjussa. Tutkimusongelman on osoittanut monikansallinen yhtiö, joka pyrkii vähentämään tarpeetonta hukkaa lähtölogistiikassaan. Tutkimus on rajattu asiakkaille räätälöityihin tuotteisiin, jotka kuljetetaan meritse. Teoreettinen viitekehys globaalisti hajaantuneiden MTO-toimitusketjujen parantamiseen kehitettiin yhdistämällä liiketoimintaprosessien johtamista, Porterin arvoketjuteoriaa, arvovirtakuvausta ja nykytilan puuta (CRT). Empiirinen tutkimus tehtiin soveltamalla konstruktiivista tutkimusotetta, sillä se mahdollistaa käytännönläheisten ongelmien tutkimisen ja olemassa olevien käytäntöjen parantamisen. Aineisto kerättiin tekemällä 10 puolistrukturoitua teemahaastattelua ja kolme ei-osallistuvaa havaintoa. Analysoimalla aineistoa ja soveltamalla teoreettista viitekehystä havaittiin viisi erilaista hukkatyyppiä, jonka nähtiin johtuvan kuudesta juurisyystä. Käytännönläheinen ratkaisu kehitettiin vähentämään tarpeetonta hukkaa prosessissa yhdistämällä sekä olemassa olevaa kirjallisuutta että aineistosta nousevia kehitysideoita. Tutkimustulokset osoittavat että monikansallinen yhtiö, jolla on globaalisti hajaantunut MTO-toimitusketju voi parantaa lähtölogistiikkaansa toiminnoilla, jotka edistävät sisäistä ja ulkoista integraatiota, koordinaatiota ja yhteistyötä sekä lisäävät prosessin ennakoivuutta. Tutkimuksella on käytännönläheistä merkitystä sekä kohdeyritykselle että muille monikansallisille yhtiöille, joilla on globaalisti hajaantunut MTO-toimitusketju. Tutkimus myös edesauttaa prosessijohtamisen ja konstruktiivisen tutkimusotteen tutkimusta, sillä tulokset osoittavat niiden soveltuvan uuteen kontekstiin.